Irrigation Kuznets Curve, governance and dynamics of irrigation development: a global cross-country analysis from 1972 to 1991 - Bhattarai, Madhusudan (International Water Management Institute, 2004)
Using a global analysis across 66 countries, this study empirically validates the presence of an Environmental Kuznets Curve (EKC) relationship for irrigation development. The resulting inverted U-shaped relationship between the level of irrigation and income implies that, water uses in irrigation and agriculture are considered more important in the early stage of development of a society. Once the economy grows, however, the relative importance of irrigation and water uses in agriculture declines, compared to water uses in other sectors.